Severe Anti-N-Methyl-D-Aspartate Receptor Encephalitis Under Immunosuppression After Liver Transplantation - Konen, Franz Felix; Schwenkenbecher, Philipp; Jendretzky, Konstantin Fritz; Hümmert, Martin Werner; Wegner, Florian; Stangel, Martin; Sühs, Kurt-Wolfram; Skripuletz, Thomas (Frontiers in Neurology, 2019)
Anti-NMDA receptor encephalitis is a rare and often therapy-responsive autoimmune disease that usually affects young adults and causes neuropsychiatric symptoms. Here, we describe a patient in her 6th decade who developed anti-NMDA receptor encephalitis while being under adequate immunosuppressive therapy following liver transplantation. Although a broad spectrum of different immunotherapies was applied and anti-NMDA receptor antibody titers gradually decreased, the clinical course could not be affected positively. Autoimmune encephalitis after transplantation is only described in few cases and not well recognized. Our case adds further evidence for anti-NMDA receptor encephalitis as the cause of neuropsychiatric symptoms even under immunosuppressive therapy in a post-transplant setting.